2020
DOI: 10.1111/1749-4877.12470
|View full text |Cite
|
Sign up to set email alerts
|

Competitor densities, habitat, and weather: effects on interspecific interactions between wild deer species

Abstract: There is a growing interest on the potential interplay between weather, habitat, and interspecific competition on population dynamics of wild herbivores. Favorable environmental conditions may buffer the negative effects of competition; conversely, competition may be expected to be stronger under harsh environmental conditions. We investigated relationships between competitor abundance, weather, and habitat cover on density and local distribution of a medium‐sized herbivore, the roe deer Capreolus capreolus, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 101 publications
0
19
0
Order By: Relevance
“…Bonnot et al 2013;Sönnichsen et al 2013;Lone et al 2014). In our study area, behaviour, distribution and density of this ungulate have been shown to be negatively influenced by interspecific competition with the fallow deer (Ferretti et al 2011;Ferretti and Fattorini 2020). Thus, roe deer avoidance of sites with high local density of fallow deer may limit the risk of encounters with wolves (Ferretti et al 2019).…”
Section: Predator-prey Interactionsmentioning
confidence: 73%
“…Bonnot et al 2013;Sönnichsen et al 2013;Lone et al 2014). In our study area, behaviour, distribution and density of this ungulate have been shown to be negatively influenced by interspecific competition with the fallow deer (Ferretti et al 2011;Ferretti and Fattorini 2020). Thus, roe deer avoidance of sites with high local density of fallow deer may limit the risk of encounters with wolves (Ferretti et al 2019).…”
Section: Predator-prey Interactionsmentioning
confidence: 73%
“…First, we examined temporal and spatial variation in feral water buffalo dung abundance. Human actions alongside rainfall, population density, water resources and forage availability are important processes that influence temporal or spatial variation in ungulate population abundances (Clutton-Brock et al 1997;Coulson et al 2000;Ferretti and Fattorini 2020;Imperio et al 2012). Similarly, we predicted that one or more of these processes could explain annual variation in water buffalo dung abundance.…”
Section: Introductionmentioning
confidence: 71%
“…However, we found a strong negative correlation between water buffalo and rusa deer population dung abundance. A decreased local abundance in one or both interacting species is often required to suggest the effects of interspecific competition (Chesson 2000;Ferretti and Fattorini 2020;Putman 1996). Two forms of competition can result in the direct and indirect resource exclusion between interacting herbivore species (Forsyth and Hickling 1998;Jung et al 2015;Ritchie et al 2009;Sinclair 1985;Valeix et al Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most remnant habitat patches, mutualistic networks for animal-mediated pollination and seed dispersal are disrupted by species loss ( Schupp et al., 2017 ; Grass et al., 2018 ) and affected by the size and quality of habitat patches ( Spiesman and Inouye, 2013 ; de Bomfim et al., 2018 ; Emer et al., 2019 ). Compared with large habitat patches, small habitat patches are unable to support the survival of most large-bodied species owing to their lower food quality and greater interspecific competition ( Hart et al., 2017 ; Ferretti and Fattorini, 2021 ). Consequently, the seed dispersal networks dominated by these large-bodied species are disrupted, thus affecting subsequent plant species recruitment ( Bregman et al., 2016 ; Donoso et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%